Making Space for the ‘Irrational’ Practice of Anthropology in Libraries - Lanclos, Donna M. (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
In this article, I extend the argument for open-ended exploratory, anthropologically informed, qualitative work in libraries that Andrew Asher and I began with “Ethnographish” (2016) and further explore and explain the paucity of open-ended exploration in library assessment and engagement work with the frame of rationality. I argue here that open-ended, exploratory anthropological work could be the kind of irrational work that can help library workers escape the neoliberal cage of rationality. If libraries are to be institutions that do not just mitigate but actively fight marginalization and inequality, we need to deeply interrogate the structures that insist on rational approaches to libraries and library work.